2010
DOI: 10.4236/health.2010.26086
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of microbial contaminants in sachet water: a public health challenge

Abstract: Accessibility and availability of fresh clean water is a key to sustainable development and essential element in health, food production and poverty reduction. In the present study, we have collected water sachet containing CM/L number and they were analysed for physical and bacteriological nature. The organisms isolated in this study were Proteus mirabilis, Klebsiella pneumoniae, Pseudomonas vesicularis and Pseudomonas aeruginosae. The harmful effects of these isolates were evidenced by antibiotic resistance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Seven sachet water samples supplied in and around Palavaran, India were subjected to microbial analysis, using the serial dilution and pour technique. Contamination was found in all the sampled water these include Proteus mirabilis, Klebsiella pneumoniae, Pseudomonas vesicularis, Pseudomonas aeruginosa (Banu and Menakuru, 2010). In Kalama region, Egypt 30% of the sachet water analyzed were contaminated with at least one coliform and pathogenic bacterium (Ennayat et al, 1998).…”
Section: Case Reports Of Contaminated Packaged Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Seven sachet water samples supplied in and around Palavaran, India were subjected to microbial analysis, using the serial dilution and pour technique. Contamination was found in all the sampled water these include Proteus mirabilis, Klebsiella pneumoniae, Pseudomonas vesicularis, Pseudomonas aeruginosa (Banu and Menakuru, 2010). In Kalama region, Egypt 30% of the sachet water analyzed were contaminated with at least one coliform and pathogenic bacterium (Ennayat et al, 1998).…”
Section: Case Reports Of Contaminated Packaged Watermentioning
confidence: 99%
“…Microbial pollution of packaged water particularly in developing countries has grave implications on public health (Warren and Mark, 1998). It threatens the population's existence causing diseases such as cholera (Njoku and Osondu, 2007;Ackah-Arthur et al, 2012), gastroenteritis (Grabow, 1996), hepatitis, typhoid fever, shigellosis (Oguntoyinbo et al, 1978;Gangarose et al, 1980;Fraechem et al, 1983;Jiburum and Mba, 2004;Kwakye et al, 2007;Banu and Menakuru, 2010; Anyamene and Ojiagu, 2014) and giardiasis (Opara and Nnadim, 2014). It could also result in symptoms such as bacillary diarrhea (Mead et al, 1999).…”
Section: Public Health Implications Of Microbial Pollution Of Commercmentioning
confidence: 99%
“…Increase in human population pose a great pressure on provision of safe drinking water especially in developing countries (Okonko et al, 2009). Consequently, water borne diseases such as cholera and typhoid often have their outbreak especially during dry season (Banu and Menakuru, 2010;Adenkunle et al, 2004). High prevalence of diarrhoea among children and infants can be due to the use of unsafe water and unhygienic practice (Oladipo et al, 2009;Tortora et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A study promoted by Sotler and collaborators [ 110 ] indicated the presence of P. aeruginosa in 33 of the 80 tested sachet water samples. The presence of this bacterium was reported in seven sachet water samples supplied in India [ 113 ]. In Abuja, Nigeria (2014), P. aeruginosa was isolated in 9.36% out of 100 brands of packaged water samples [ 114 ].…”
Section: Antibacterial Potential Of Bioactive Compounds From Macromentioning
confidence: 99%